2019
DOI: 10.3991/ijet.v14i06.10160
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient English MOOC Teaching Model Based on Frontline Education Analysis

Abstract: The MOOC teaching model is a teaching method emerging with the rapid devel-opment of the Internet, characterized by openness, large scale, interactivity and feedback. However, at present, English is mostly taught in the traditional cram-ming model, which has such problems as fossilized teaching content, small cor-pus, single teaching method and lack of a feedback mechanism. Under this mod-el, students lack the enthusiasm and initiative in English learning. By introducing MOOC, this paper innovates a new teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…By using data technology, some large libraries launch online teaching, online self-test and online interactive games, develop nonprofit or commercial App and carry out public information literacy education in a variety of ways. For example, the TEDA Library in Tianjin, China [13][14] offered a "Digital Readability: TEDA Open Class for Information Literacy", to generalize the theory of information literacy, promote the information awareness and information ability of the public and draw up corresponding public incentives.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…By using data technology, some large libraries launch online teaching, online self-test and online interactive games, develop nonprofit or commercial App and carry out public information literacy education in a variety of ways. For example, the TEDA Library in Tianjin, China [13][14] offered a "Digital Readability: TEDA Open Class for Information Literacy", to generalize the theory of information literacy, promote the information awareness and information ability of the public and draw up corresponding public incentives.…”
Section: State Of the Artmentioning
confidence: 99%
“…Reciprocal teaching [14] is a new teaching method that emphasizes the unity between communication, cooperation and computer use. Today, the rapid development of electronic technology and multimedia interaction has given birth to reciprocal teaching.…”
Section: The Application Of Vr Technology In the Reciprocal Teaching mentioning
confidence: 99%
“…The project was beneficial to the hidden curriculum in terms of teamwork promotion, personal and group challenges, contact with the local community and other students, and science popularization. Gao et al [7] proposed that biomechanics should pay attention to the development of experiment teaching materials and conducted teaching reform experiment by using "hurdling" as the teaching case on the basis of information-based electronic textbooks. They found that the experimental class had better performance and higher accuracy of skill mastery than the control group.…”
Section: State Of the Artmentioning
confidence: 99%
“…With the rapid development of modern science and technology, reasonable use of new media technology can impart knowledge to students through informatization methods [3]. In the teaching of psychology courses in colleges, the special advantage of new media can be integrated and used to improve the overall quality of psychology teaching for college students.…”
Section: Introductionmentioning
confidence: 99%